The Influence of the Inquiry Project-Based Learning Model on Critical Thinking Skills in Early Childhood: A Quantitative Experimental Study - Yuliani, Roficha; Abd Jabar, Cepi Safruddin; Maryatun, Ika Budi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This study aims to measure the impact of the Inquiry Project-Based Learning model on the critical thinking abilities of children aged 5-6 years at Budya Wacana Kindergarten, Yogyakarta. The research methodology adopted an experimental quantitative approach with a pre-experimental design, specifically the one-group pretest-posttest design. The sample consisted of 35 children selected through the Total Sampling technique. Data were collected using observation sheets and documentation, with instruments focusing on five indicators of critical thinking ability. Data analysis employed normality tests, homogeneity tests, and paired sample t-tests using SPSS 25. The results indicated a significant increase in posttest essential scores of thinking (86.03) compared to the pretest (47.60), with a t-value of -31.352 and a significance of 0.000. These findings affirm the effectiveness of this learning model in enhancing early childhood critical thinking skills while also opening opportunities for further research in early childhood education. This study has significant implications for educational practice, suggesting integrating the Inquiry Project-Based Learning method into the curriculum and highlighting the need for teacher training to implement this method. However, limitations exist, such as focusing on a limited sample size and not evaluating long-term effects.